Shear Bond Strength of Orthodontic Brackets to Zirconium Oxide Infrastructure Treated with Er:YAG, Nd:YAG, and KTP Lasers: An Experimental Study - Melih Ulgey; Zeynep Çoban Büyükbayraktar; İhsan Hubbezoğlu; Oguzhan Gorler (Cumhuriyet University, 2020)
Objectives: The aim of the present study was to investigate the shear bond strength of orthodontic brackets to zirconium oxide infrastructures treated with erbium-doped yttrium aluminum garnet (Er:YAG), neodymium-doped yttrium aluminum garnet (Nd:YAG) and potassium titanyl phosphate (KTP) laser modalities in in vitro settings. Materials and Methods: A total of 40 zirconium oxide infrastructures were prepared with CAD/CAM technology in accordance with ISO 11405 standard. The specimens were divided into 4 groups as following: Er:YAG, Nd:YAG, KTP, and control groups (n=10). Prior to the application of cementation of orthodontic brackets, the surfaces of the zirconium oxide infrastructures were irradiated using selected laser modailites. Shear bond strength tests were performed on each specimen by using a universal testing machine. Results: The shear bond strength value of Er:YAG laser group was significantly higher than those of all other groups (p<0.05); although the bonding strength of Nd:YAG laser was higher than that of the KTP laser, this difference was not reached statistical significance (p>0.05). The bonding strength values of Nd:YAG laser group were significantly higher than that of the control group (p<0.05); and the the bonding strength values of KTP laser group were significantly higher than that of control group (p<0.05). Conclusion: The bond strength between the orthodontic brackets and zirconium oxide infrastructures was improved upon using all the laser modalities in the present study, among which, application of the Er:YAG laser was the most successful.